Effect of soil application of nickel on growth, micronutrient concentration and uptake in barley (Hordeum vulgare L.) grown in Inceptisols of Varanasi. (2nd January 2018) - Kumar, Omkar; Singh, S. K.; Singh, A. P.; Yadav, S. N.; Latare, A. M.
ABSTRACT: A pot experiment was conducted in a glass house on low nickel containing alluvial soil in the Department of Soil Science and Agricultural Chemistry, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, during 2012–13 and 2013–14, to study the response of barley to soil application of nickel (Ni). There were ten treatments of Ni (0, 2.5, 5, 10, 15, 20, 30, 40, 50 and 60 mg kg −1 ) studied with recommended dose of fertilizers nitrogen, phosphorus, potassium and sulfur (N:P:K:S :: 40:30:30:20 mg kg −1 ).The results showed a significant increase in plant height, number of tillers, chlorophyll content, straw and grain yield, and 1, 000 grains weight with application of 10 mg Ni kg −1 soil during both years of study. The micronutrient concentration and uptake in straw and grain increased with application of <15 mg Ni kg −1 soil and beyond that declined significantly. Diethylenetriaminepentaacetic acid-extractable micronutrient iron, manganese, copper, zinc and nickel (Fe, Mn, Cu, Zn and Ni) content in soil increased with increasing level of Ni. The maximum urease activity in post-harvest soil was noticed with application of 40 mg Ni kg −1 soil. The microbial population viz. bacteria, fungi and actinomycetes were higher with 5, 30 and 10 mg Ni kg −1 soil, respectively.